Motivation for the Family Visit and On-the-Spot Activities Shape Children’s Learning Experience in a Science Center - Tõugu, Pirko (Frontiers in Psychology, 2021)
Children’s learning often happens in the interactions with more knowledgeable members of the society, frequently parents, as stated by the sociocultural theory. Parent-child conversations provide children with a new understanding and foster knowledge development, especially in informal learning contexts. However, the family conversations in museums and science centers can be contingent on the motivation for the family visit or the activities organized on the spot. In order to establish how family motivation and on-the-spot activities influence children’s informal learning experience, the present study was carried out in a family science center. The study focused on children’s learning experience in a hands-on exhibit featuring objects that allow for the exploration of the concepts of sound waves and light. Thirty-nine 7-10-year-old children (21 boys, 18 girls) and their families participated in the study. Twenty families received a worksheet to prompt an experimentation activity with one of the light exhibits. Motivation for the family visit was probed at the end of the visit. The target children of the families wore a GoPro HERO 5 camera attached to a chest harness throughout their visit. The video was coded for family interaction and experimentation with the light exhibit. Family conversations were coded for open-ended questions, responses to open-ended questions, explanations, associations, attention directing, and reading signage aloud. Family motivation for the visit was related to the quality of family conversation during the visit. The experimentation activity prompt did not affect the likelihood of noticing and engaging with the particular exhibit. At the same time, it did affect the quality of engagement: children who received the experimentation activity prompt were more likely to explore the effects the exhibit provided and experiment rather than play with the exhibit. Family motivation and on-the-spot activities are discussed as two possible factors to influence children’s learning experience in science centers.